2013
DOI: 10.1088/0268-1242/28/10/105025
|View full text |Cite
|
Sign up to set email alerts
|

Opportunities and pitfalls in patterned self-catalyzed GaAs nanowire growth on silicon

Abstract: Periodic arrays of self-catalyzed GaAs nanowires (NWs) were grown on Si substrates by gas source molecular beam epitaxy (GS-MBE) using patterned oxide templates. The various challenges of the patterning process that result in undesired outcomes are described, such as pattern transfer by wet/dry etching, oxide thickness variations, and native oxide re-growth. Transmission electron microscopy (TEM) results are used to illustrate each case. In particular, we show that a linearly increasing length-radius distribut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
39
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(41 citation statements)
references
References 26 publications
2
39
0
Order By: Relevance
“…6. The recurrent observation of such an interface layer has been described in other works, where though successful growth of GaAs nanowires on patterned silicon dioxide is not related to the presence of interstitial oxide at the SiO 2 hole opening [42][43][44]. However the role of Si/SiO 2 -interface in the growth mechanism is still not fully understood and requires further investigation.…”
Section: Discussionmentioning
confidence: 82%
“…6. The recurrent observation of such an interface layer has been described in other works, where though successful growth of GaAs nanowires on patterned silicon dioxide is not related to the presence of interstitial oxide at the SiO 2 hole opening [42][43][44]. However the role of Si/SiO 2 -interface in the growth mechanism is still not fully understood and requires further investigation.…”
Section: Discussionmentioning
confidence: 82%
“…More generally, our procedure combines features of the deterministic VLS growth of nanowires and random selfassembly of surface islands. We have shown that the usual assumption, an instantaneous nucleation of nanowires [17,25,[31][32][33] does not work for Ga-catalyzed growth of GaAs nanowires, and could significantly change the deterministic growth picture of VLS nanowires in general. Figure 6.…”
Section: Resultsmentioning
confidence: 93%
“…Pre-patterning the substrate would be an approach to control density. However, such a technique is technologically demanding and presents several open challenges [15][16][17]. Furthermore, a regular array would not work on all incident angles due to diffraction effects [18].…”
Section: Introductionmentioning
confidence: 99%
“…More detailed characterization on the length and diameter distribution is given in the appendix. [20][21][22]. The same device is much more straight forward for InAs, though the small band gap hinders the achievement of high efficiency.…”
Section: Introductionmentioning
confidence: 99%